Carbon-cycle perturbation in the Middle Jurassic and accompanying changes in the terrestrial paleoenvironment - Hesselbo, S; Morgans-Bell, H; McElwain, J; Rees, P; Robinson, SA; Ross, C (2003)
Carbon-isotope analyses of fossil wood from the Middle Jurassic Ravenscar Group, Yorkshire, NE England, reveal a significant excursion toward light isotopic values (δ13C change of -3 to -4‰) at about the Aalenian-Bajocian boundary (∼174 Ma). A positive carbon isotopic excursion is also shown for the middle Bajocian (∼170 Ma) but is less clearly defined. These isotopic patterns are very similar to the few published marine carbonate records available for this time, in particular one based on belemnites from the Hebrides basin, NW Scotland, and others from pelagic limestones in Italy. The similarity of the terrestrial and marine isotope curves is an indication that the observed isotopic signal is a global phenomenon. Through parts of the Ravenscar Group (the Scarborough Formation), supplementary data from bulk organic carbon and palynofacies analysis confirm that isotopic curves based on bulk analyses may be strongly influenced by the balance of terrestrial versus marine organic matter present in the samples. The negative isotope excursion at the Aalenian-Bajocian boundary marks a change from charcoal to coal as the dominant preservational mode of the macroscopic wood fossils, which is interpreted here as a shift to a more continuously humid climate in the Early Bajocian. Upsection, charcoal once again becomes common, reflecting a return to more fireprone (presumably seasonally arid) environments in the middle Bajocian. Paradoxically, floral assemblages associated with the lithological unit in which the negative excursion occurs display characteristics that would normally be interpreted as adaptations to water stress brought about by relative aridity or salinity. Preliminary analyses of leaf stomatal densities show some evidence of raised pCO2 relative to background values at about the level of the negative excursion.